KKN Moderasi Beragama: Membantu Guru Pendidikan Agama Islam Dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) Kurikulum 2013 - Kariadi, Atman; Nuzuli, Ahmad Khairul; Oktaviana, Winda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The lesson plan or what is known as RPP is a form of lesson plan that will be carried out by educators in learning activities, in this case an educator has paid close attention, both material, assessment, time allocation, learning resources, and learning methods to be used . The general objective of this research is to describe how an Islamic Religious Education subject teacher makes and compiles a Learning Planning Plan (RPP). This research uses a research approach using a literature review technique of listening, where one of the listening techniques is the note-taking technique. Data collection techniques are by using literature books or library materials, then recording them or quoting the opinions of experts in the book to strengthen the theoretical basis in writing articles and using the descriptive content analysis study method. The results of the research show that the ability of Islamic Religious Education teachers in preparing Learning Planning Plans (RPP) at SD Negeri 01 Bride can be said to be "very good" with 2 days the author guides and assists PAI teachers in preparing RPP for the 2013 curriculum.